Targeting the NLRP3 inflammasome abrogates cardiotoxicity of immune checkpoint blockers - Ping Li; Zhen Qin; Yang Lu; Jiamin Gao; Zhenwei Wang; Ge Zhang; Han Yang; Yachen Hou; Dashuai Wang; Pengchong Du; Yunzhe Wang; Quanzhou Chen; et al. (Journal for ImmunoTherapy of Cancer)
Background Immune checkpoint inhibitors (ICIs) have revolutionized the treatment of many malignant tumors. However, ICI-induced hyper-immune activation causes cardiotoxicity. Traditional treatments such as glucocorticoids and immunosuppressants have limited effectiveness and may even accelerate tumor growth. This study aimed to identify approaches that effectively reduce cardiotoxicity and simultaneously preserve or enhance the antitumor immunity of ICI therapy.Methods ICI injection in melanoma-bearing C57BL/6J female mice was used to simulate cardiotoxicity in patients with tumor undergoing immune therapy. MCC950 was used to block nod-like receptor protein 3 (NLRP3) inflammasome activity. Echocardiography, immunofluorescence, flow cytometry, and reverse transcription quantitative polymerase chain reaction were used to assess cardiac function, immune cell populations, and inflammatory factor levels. Bulk and single-cell RNA sequencing was used to detect the changes in cardiac transcriptome and immunological network.Results NLRP3 inhibition reduced inflammatory response and improved cardiac function. Notably, NLRP3 inhibition also resulted in a pronounced suppression of tumor growth. Single-cell RNA sequencing elucidated that MCC950 treatment reduced the cardiac infiltration of pathogenic macrophages, cytotoxic T cells, activated T cells, and their production of inflammatory cytokines, while enhancing the presence of reparative macrophages and naive T cells. In addition, MCC950 attenuated cardiotoxicity induced by dual programmed cell death protein 1 (PD-1) and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) immunotherapy and promoted tumor regression, and showed efficacy in treating established cardiotoxicity.Conclusions Our findings provide a promising clinical approach for preventing and treating cardiotoxicity induced by ICIs, dissociating the antitumor efficacy of ICI-based therapies from their cardiotoxic side effects.